지속 가능한 도시 측면에서 바라본 3기 신도시 계획특성 - 3기 신도시 시범지구를 중심으로 - 국승재(Seung-Jae Kook); 송정석(Jeong-Seok Song); 이효원(Hyo-Won Lee) (KIEAE Journal, 2024)
Purpose: By comparing and analyzing the characteristics of sustainable planning for urban space and ecological environment in the 3rd new city, we aim to identify changes and alternatives to the elements of housing development planning to proceed in the future. Method: We analyze the characteristics of the case by identifying differentiated planning elements applied to the urban space and ecological environment of the pilot district in the 3rd new city, aiming to create a shared city (people, streets, and community). Result: The competition guidelines for the pilot district set a people-centered, street-centered shared city as the basic direction, and differentiated planning characteristics for each design district specialized for regional characteristics were applied. The selected plans confirmed the results of the analysis that specified and presented the differentiated planning characteristics from the indicators of the sustainable planning standards in which the commonly suggested people-centered eco-friendly space becomes daily life. In addition, the third new city plans to make the process of ecological space becoming daily life a three-dimensional and complex space through the integrated urban architecture plan. KCI Citation Count: 0